Road Noise Levels in Urban Environment Compared to Specification Limits. The Case of the City of Larissa, Greece - Papadimitriou, Emmanouil A.; Papageorgiou, Grigorios P.; Alamanis, Nikolaos; Diakosavva, Theodosia-Niki (Periodica Polytechnica Civil Engineering, 2020)
Greece, as well as other developed countries, is facing the growing problem of road traffic noise. It stands for a severe problem in the urban areas of the country, including the city of Larissa. The root cause is the huge increase in traffic volume and the lack of adequate urban infrastructure planning. Estimation of the level of road traffic noise is usually conducted using acoustic meters. It is widely accepted that most of the cities’ population is exposed to high noise levels due to controversial traffic capacity. Moreover, high noise levels are strongly related to phycological and neurological diseases. Thus, it is of utmost importance, the road noise levels to be lower than dictated by relevant specification limits. To develop better noise-environment policies, relative research should focus on the measurement of in-situ noise levels, so as appropriate for each case corrective measures to be taken. The present paper examines the noise levels of a center road of the 5th Greek city, in terms of population, compared to worldwide adopted noise specification limits. The clear aim stands for finding the percentage of road noise that exceeds commonly accepted threshold values, namely limit values of European Union and World Health Organization. The results of this research strongly indicate that measured noise values override upper limit values in a certain extent.